Shame in SLA: Narrative insights from French learners of FLs - GALMICHE, Dominique (2021)
The experience of shame is excruciatingly painful as it involves a loss of self-esteem and a diminished sense of self. Research in the fields of psychology and psychoanalysis has found links between shame and a diversity of pathologies, and it has been shown to impact individuals’ psychological well-being in a negative way. It is proposed here that the affective variable of shame has its place as a valid subject for investigation into the multifaceted and complex phenomena underlying the acquisition and use of an additional language as it may interfere with second language (L2) learning. The current research in progress is one of the rare exploratory studies devoted to shame in second language acquisition (SLA) and, to the author’s knowledge, the only one so far to have been conducted in the context of the French foreign language classroom. Its aim is to explore the nature, antecedents and consequences of this phenomenon from the perspective of four focal French learners of English as a Second Language (ESL). Through in-depth, semi-structured, face-to-face interviews, 34 students recalled their negative L2-related experiences and their thought-provoking remarks interestingly revealed that the language classroom can generate a number of occasions for learners to experience shame and other negative and pathogenic emotions, like anxiety and humiliation, which in some cases may deter them from engaging in the long-term learning of foreign languages. Among the various skills, speaking the target language was reported to be the most liable to elicit shame because of the greater likelihood of displaying an incompetent self to others, as compared with writing skill. It is argued here that taking shame into consideration in the teaching practice will offer new insights into the non-linear process of acquiring another language to researchers and practitioners alike, and provide a better understanding of what takes place in the language classroom. It is hoped that the current research will help teachers recognize shame-indicating cues in their learners and address them in a systematic way. The findings provided a valuable individual-level analysis of French students’ experiences of shame in L2 educational contexts and the investigation moves away from single cause-effect explanations for learner shame and suggests that there are several different routes through which shame emerges, and these routes (i.e. ‘attractors’ in a Dynamic Systems Theory perspective) are multifarious and so multiple and profoundly ingrained, both educationally and culturally in the French context, that shame has crystallized into a semi-permanent attractor state within language classrooms. Finally, this thesis suggests to build on the findings of the current study and stresses the need for further research on this complex and multifaceted emotion.